2017
DOI: 10.3389/fmars.2016.00280
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wetland Decline on Decreasing Dissolved Organic Carbon Concentrations along the Mississippi River Continuum

Abstract: Prior to discharging to the ocean, large rivers constantly receive inputs of dissolved organic carbon (DOC) from tributaries or fringing floodplains and lose DOC via continuous in situ processing along distances that span thousands of kilometers. Current concepts predicting longitudinal changes in DOC mainly focus on in situ processing or exchange with fringing floodplain wetlands, while effects of heterogeneous watershed characteristics are generally ignored. We analyzed results from a 17-year time-series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 48 publications
7
24
0
Order By: Relevance
“…Although our wet season sampling was conducted after the peak in the annual hydrograph, our data shows a longitudinal increase in DOC concentrations (Table 2 and Figure 5), partly due to the increase in hydrological connectivity that promotes the longitudinal input of DOC from the tributaries [Singh et al, 2015;Lambert et al, 2016b]. The importance of wetlands as a constant source of DOC is documented by Duan et al [2017], who found that downstream decreases in DOC for the Mississippi River were due to the loss of wetlands caused by changes in land use.…”
Section: Role Of Hydrologic Connectivity On Dom Characteristicsmentioning
confidence: 85%
See 1 more Smart Citation
“…Although our wet season sampling was conducted after the peak in the annual hydrograph, our data shows a longitudinal increase in DOC concentrations (Table 2 and Figure 5), partly due to the increase in hydrological connectivity that promotes the longitudinal input of DOC from the tributaries [Singh et al, 2015;Lambert et al, 2016b]. The importance of wetlands as a constant source of DOC is documented by Duan et al [2017], who found that downstream decreases in DOC for the Mississippi River were due to the loss of wetlands caused by changes in land use.…”
Section: Role Of Hydrologic Connectivity On Dom Characteristicsmentioning
confidence: 85%
“…The importance of wetlands as a constant source of DOC is documented by Duan et al . [], who found that downstream decreases in DOC for the Mississippi River were due to the loss of wetlands caused by changes in land use.…”
Section: Discussionmentioning
confidence: 99%
“…For example, alterations to floodplain networks can reduce aquatic DOC levels, which limits the presence of environments that promote a reduction in nutrient concentrations via denitrification (Philip and Townsend, 2010). Anthropogenic hypoxia is often attributed to agricultural inputs of fertilizers (Rabotyagov et al, 2014), but wetland loss in managed watersheds such as the Mississippi River is likely another important factor to consider (Mitsch et al, 2005;Schramm et al, 2009;Duan et al, 2017). Likewise, increased export of terrestrially-derived OM due to watershed perturbations and its subsequent decomposition in coastal waters is not currently considered to be a factor driving hypoxia, but may play an important role.…”
Section: Estuaries and Coastal Oceansmentioning
confidence: 99%
“…While DOM processing through photochemistry is expected to decrease in the lower watershed due to increasing turbidity, the association of C4 with higher stream order compared to land use indicates to a small extent that photochemical alteration of DOM in the lower Altamaha River watershed might still be pertinent. We were able to show with RDA that a combination of both watershed land use and the traditional RCC could explain roughly 50% of the spatial variability of DOM composition in the Altamaha River watershed as described by both EEM-PARAFAC and FTICR-MS. Just as watershed land use has been described as good predictors of DOM composition in other systems [83][84][85] , it also explained a higher degree of variability in the Altamaha River watershed compared stream order, highlighting the need to further consider the controls of land use on DOM composition in future adaptations of the RCC.…”
Section: Spatial Variability In Dom Composition: Land Use Vs Stream Omentioning
confidence: 99%
“…Longitudinal shifts in DOM quality have been linked to clear shifts in watershed land cover80 , but more specifically to watershed connectivity with wetlands[81][82] . In the Mississippi River, loss of wetlands downstream generally resulted DOM becoming less aromatic in character83 . In fact, wetlands are generally considered good predictors of DOC concentration[84][85] as well as DOM composition where a higher proportion of aromatic, humic like material are sourced from areas with high degrees of wetland cover29,86 .…”
mentioning
confidence: 99%